Relationship of Moral Climate and Moral Distress with Job Involvement among Nurses Working in Hospitals Affiliated with Hamadan University of Medical Sciences in 2020 - Mahsa Eslami-Panah; Mohammad Torabi; Fariba Borhani; Abbas Abbaszadeh (Hamadan University of Medical Sciences, 2022)
Background and Objective: Today, due to advances in science and technology and dealing with various moral issues, nurses experience more distress. Therefore, the behavioral framework of nurses and the quality of services provided to patients can be influenced by the ethical climate in the hospital. Moreover, the moral distress and moral climate in the hospital can influence the nurses' job involvement. Therefore, this study was conducted to investigate the relationship between moral climate and moral distress with the job involvement of nurses working in hospitals affiliated with Hamadan University of Medical Sciences, Hamedan, Iran. Materials and Methods: This descriptive-correlational study was conducted on 140 nurses working in hospitals affiliated with Hamadan University of Medical Sciences. Data collection tools included a demographic information form, Hospital Ethical Climate Survey, Revised Moral Distress Scale, and Kanungo Job Involvement Questionnaire. Data were analyzed using descriptive and inferential statistics in SPSS 23 software. Results: The mean score of the intensity of moral distress was 3.81±1.25 and the frequency of moral distress was 2.6±1.3. The mean scores of moral climate and job involvement were 3.91±1.68 and 2.71±1.1, respectively. There was a significant positive relationship between moral climate and nurses' job involvement (r=0.41, P<0.001). A significant negative relationship was observed between the intensity of nurses' perceived moral distress and their job involvement (r=- 0.36, P=0.03). Conclusion: According to the research findings, it can be noted that reducing moral distress and improving the hospital's moral climate can play important roles in improving nurses' job involvement.